2000
DOI: 10.2169/internalmedicine.39.407
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Three Fatal Cases of Non-specific Interstitial Pneumonia.

Abstract: Wedescribe the clinical courses of the 3 fatal patients (2 females and 1 male) with idiopathic non-specific interstitial pneumonia (NSIP) among 24 patients with NSIP. Lung biopsies were diagnosed to be NSIP group II in all patients. The clinical courses from onset to death of these 3 patients were 41 months, 46 months, and 91 months. A follow-up chest CT demonstrated no apparent honey-combformation. Wefound that i) about 20%of patients with NSIP died of respiratory failure, ii) in the chest CT findings, appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…It seems difficult to detect significant findings as prognostic factors, however. Even in fatal NSIP cases, a follow-up chest CT demonstrated no apparent honeycombing [38]. Another report concluded that patients with interlobular interstitial thickening and traction bronchiectasis showed favorable response to therapy [28].…”
Section: Chest Radiograph and Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems difficult to detect significant findings as prognostic factors, however. Even in fatal NSIP cases, a follow-up chest CT demonstrated no apparent honeycombing [38]. Another report concluded that patients with interlobular interstitial thickening and traction bronchiectasis showed favorable response to therapy [28].…”
Section: Chest Radiograph and Scanningmentioning
confidence: 99%
“…The presence of desaturation during a 6-minute walk test was associated with an increased hazard of death after adjusting for age, sex, smoking, baseline diffusion capacity for carbon monoxide, forced vital capacity (FVC), and resting saturation in patients with IPF/UIP (n = 83) and NSIP (n = 22) [38]. Changes in physiologic variables over 6 and 12 months may be more accurate prognostic information than baseline values alone [40].…”
Section: Pulmonary Function Tests and Baseline And Serial Changesmentioning
confidence: 99%
“…(1-18)) and UIP patients (lymphocytes 6 (0-38), neutrophils 8.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), eosinophils 5 (0-11)). There was no statistical difference in the total and differential cell counts between the two groups (Mann-Whitney test p=NS for all cell types; fig.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
“…However, although initial reports showed large differences in mortality between the two groups [7][8][9], later studies documented a high 5-and 10-yr mortality rate in fibrotic NSIP [5,10]. Cellular NSIP, by contrast, has a 10-yr survival of 100% [5,6].…”
mentioning
confidence: 99%
“…Clubbing was reported in 10% of the patients with NSIP and in 65% of IPF cases, including UIP. [1213] It appears that the clinical presentation of NSIP and UIP are similar.…”
mentioning
confidence: 99%